PENINGKATAN MINAT BELAJAR SISWA DALAM MATA PELAJARAN EKONOMI MELALUI STRATEGI PEMBELAJARAN AKTIF TIPE INDEX CARD MATCH DI KELAS X MIPA 2SMAN 1 PASAMAN - NULFALINDA NULFALINDA (JURNAL MANAJEMEN PENDIDIKAN, 2019)
Based on the learning outcomes of Class X MIPA 2 students of SMAN 1 Pasaman in economic subjects it was found that student interest in economic subjects was still low. The purpose of this study was to describe and obtain information about increasing student learning interest in economic subjects through the Active Learning Strategy Index Card Match Type in Class X MIPA 2 SMAN 1 Pasaman. This research is a class action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 32 students of Class X MIPA 2 SMAN 1 Pasaman. Research data were collected using a test sheet. Data were analyzed using percentages. Based on the results of research and discussion that has been stated, it can be concluded that the Active Learning Strategy Index Card Match Type can increase student learning interest in economics in Class X MIPA 2 SMAN 1 Pasaman. Student learning interest in the first cycle was 69.67, increasing to 84.36.